The co-occurrence of water insecurity and food insecurity among Daasanach pastoralists in northern Kenya - Hilary J Bethancourt; Zane S Swanson; Rosemary Nzunza; Sera L Young; Luke Lomeiku; Matthew J Douglass; David R Braun; Emmanuel K Ndiema; Herman Pontzer; Asher Yoel Rosinger (Cambridge University Press, 2023)
Abstract Objective: Water plays a critical role in the production of food and preparation of nutritious meals, yet few studies have examined the relationship between water and food insecurity. The primary objective of this study, therefore, was to examine how experiences of household water insecurity (HWI) relate to experiences of household food insecurity (HFI) among a pastoralist population living in an arid, water-stressed region of northern Kenya. Design: We implemented the twelve-item Household Water Insecurity Experiences (HWISE, range 0-36) Scale and the nine-item Household Food Insecurity Access Scale (HFIAS, range 0-27) in a cross-sectional survey to measure HWI and HFI, respectively. Data on socio-demographic characteristics and intake of meat and dairy in the prior week were collected as covariates of interest. Setting: Northern Kenya, June-July 2019. Participants: Daasanach pastoralist households (n 136) from seven communities. Results: In the prior 4 weeks, 93·4 % and 98·5 % of households had experienced moderate-to-severe HWI and HFI, respectively. Multiple linear regression analyses indicated a strong association between HWI and HFI. Each point higher HWISE score was associated with a 0·44-point (95 % CI: 0·22, 0·66, P = 0·003) higher HFIAS score adjusting for socio-economic status and other covariates. Conclusions: These findings demonstrate high prevalence and co-occurrence of HWI and HFI among Daasanach pastoralists in northern Kenya. This study highlights the need to address HWI and HFI simultaneously when developing policies and interventions to improve the nutritional well-being of populations whose subsistence is closely tied to water availability and access.